The Human Relation With Nature and Technological Nature - Manikumar,; Babu, Suresh (The journal of contemporary issues in business and government, 2019)
Two global phenomena are profoundly transforming human existence: the deterioration, if not complete annihilation, of enormous areas of the natural world, and unprecedented levels of human population growth. a progression in technical advancement At the intersection of these two tendencies is lies the nature of technology—technologies that, in many forms, to mediate, enhance, or imitate the natural environment in many ways Videos are a good illustration of technological nature at the moment. as well as real-time cameras of nature, robot animals, and immersive experiences Virtual environments are those that are created in a virtual environment. Does it make a difference in terms of the physical and mental health? the psychological well-being of the human species as it exists in the present Is it possible that nature is being supplanted by technological nature? As a result of the We use the following as the foundation for our tentative response (which is "yes"). Accounts of the evolutionary and cross-cultural developmental processes of The relationship between humans and nature, as well as some new psychology studies on the consequences of technological nature Finally, we explore the issue—as well as some future study directions— "Environmental generational amnesia," as the term is used. The source of worry is that, by progressively becoming used to the absence of true nature Humans will get more technologically advanced as time goes on. reduce the baseline for what qualifies as a crime across generations by full measure of the human condition and of human potential thriving.